weak ties, strong ties and ambidextrous innovation - Huang, bingjie (bj) (2011)
Social capital plays an important role in explaining inter-organizational learning and knowledge acquisition, but little research discuss the relationship between social capital and exploitative and explorative innovation. In response, this dissertation examines the effect of weak ties and strong ties on young firms’ innovation and performance through single case study of Skeleton Video Production, a video company. The results show not only that firms can manage mixed ties to pursue ambidextrous innovation to balance its long-term and short term development, but also that weak ties’ effect on novel information is overstated in previous research. This study also reveals that based on strong ties’ influence on knowledge transfer, young firms can develop distant networks into close networks to better exploit an opportunity after exploring it. The evidence shows, too, a diverse access to customer network enhances firms’ ability of learning and innovation.